Germline variants and somatic mutation signatures of breast cancer across populations of African and European ancestry in the US and Nigeria. Issue 12 (27th June 2019) - Wang, Shengfeng; Pitt, Jason J.; Zheng, Yonglan; Yoshimatsu, Toshio F.; Gao, Guimin; Sanni, Ayodele; Oluwasola, Olayiwola; Ajani, Mustapha; Fitzgerald, Dominic; Odetunde, Abayomi; Khramtsova, Galina; Hurley, Ian; et al.
Abstract : Somatic mutation signatures may represent footprints of genetic and environmental exposures that cause different cancer. Few studies have comprehensively examined their association with germline variants, and none in an indigenous African population. SomaticSignatures was employed to extract mutation signatures based on whole‐genome or whole‐exome sequencing data from female patients with breast cancer (TCGA, training set, n = 1, 011; Nigerian samples, validation set, n = 170), and to estimate contributions of signatures in each sample. Association between somatic signatures and common single nucleotide polymorphisms (SNPs) or rare deleterious variants were examined using linear regression. Nine stable signatures were inferred, and four signatures (APOBEC C>T, APOBEC C>G, aging and homologous recombination deficiency) were highly similar to known COSMIC signatures and explained the majority (60–85%) of signature contributions. There were significant heritable components associated with APOBEC C>T signature ( h 2 = 0.575, p = 0.010) and the combined APOBEC signatures ( h 2 = 0.432, p = 0.042). In TCGA dataset, seven common SNPs within or near GNB5 were significantly associated with an increased proportion (beta = 0.33, 95% CI = 0.21–0.45) of APOBEC signature contribution at genome‐wide significance, while rare germline mutations in MTCL1 was also significantly associated with a higher contribution of this signature ( p = 6.1 × 10 −6 ). This is the first study to identify associations between germline variants and mutational patterns in breast cancer across diverse populations and geography. The findings provide evidence to substantiate causal links between germline genetic risk variants and carcinogenesis. Abstract : What's new? Women of African ancestry are more likely to be diagnosed with clinically aggressive breast cancer than women of European or Asian ancestry. Here, the authors examined associations between germline variants and mutational signatures in breast cancers across different ethnicities, especially in a unique sample set of indigenous African women. They identified four stable mutational signatures that explained the majority of tumor mutations, leading to a better understanding of the complex interplay between germline genetics and somatic mutations across different ethnicities.